2010
DOI: 10.1186/1472-6920-10-56
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clerkship in the attitudes toward psychiatry among Portuguese medical students

Abstract: BackgroundGiven the shortage of human resources and the launching of a new Mental Health Plan, recruitment of psychiatrists is currently a major concern in Portugal, as well as in several other countries. Medical students' attitude toward psychiatry has been pointed as a predictor of recruitment. This study aims to evaluate the medical students' perception of psychiatry before and after a clerkship, and the impact on their intention to pursue psychiatry as a future specialty option.MethodsTwo self-report quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…According to the existing literature on the subject, education can produce some changes to medical students’ attitudes toward psychiatry [22,30]. We suggest that all medical schools should consider supplying appropriate education or counseling about career choices to enhance the image of psychiatry (or any other specialty), which would help modify students’ attitudes and opinions toward different specialties and allow a less biased career choice.…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing literature on the subject, education can produce some changes to medical students’ attitudes toward psychiatry [22,30]. We suggest that all medical schools should consider supplying appropriate education or counseling about career choices to enhance the image of psychiatry (or any other specialty), which would help modify students’ attitudes and opinions toward different specialties and allow a less biased career choice.…”
Section: Discussionmentioning
confidence: 99%
“…The scale consisted of 30 statements, 15 of them were negatively stated with the other 15 were positively stated. The positively stated items (i.e., questions 4,5,9,12,14,15,18,20,23,25,[27][28][29] were reversed by subtracting the score from 6. The instrument showed good internal consistency for this study (Cronbach's alpha = 0.810).…”
Section: Materials and Method:-mentioning
confidence: 99%
“…Only 48.35 % acknowledged psychiatry as an important part of the curriculum, with the majority (62.38 %) didn't consider their undergraduate psychiatric training to be valuable, which may be due to the fact that 74.62 % believe that psychiatry is so amorphous that it cannot be taught effectively. Although not examined in this study, several studies have pointed to the positive effect of psychiatric clerkship or attachment among medical students and interns [27,28,29]. In a study done in Saudi Arabia [6], the students showed a favorable attitude after they have had some experience in psychiatry.…”
Section: Positive Attitudementioning
confidence: 99%
“…The higher number of female respondents in our study correlates with the national and international 'feminisation' trend of increased female enrolments for medical studies. [10,13,23,24] There were fewer junior 5th-year respondents than senior respondents, which reflects the spread of clinical rotations over a period of 18 months, starting in the middle of the 5th year. The absence of significant differences between the different scores for male and female, junior and senior students, or for the rotations at different times of the year is indicative of the common exposure that would be expected in a psychiatry training setting.…”
Section: Articlementioning
confidence: 99%
“…[8,9] Most other reported surveys among psychiatry students relate to final-year students' attitudes to psychiatry or psychiatric illness, or to psychiatry as a career choice. [10][11][12][13][14][15][16][17] One study conducted among 85 preregistration house officers in Norway had more similar objectives to those of our study, namely getting a sense of the learning benefits and learning environment of a psychiatry rotation. [18] This article reports on the findings of undergraduate medical students' evaluation of the final psychiatry rotation at the University of…”
mentioning
confidence: 99%